Effect of protrusion structure on the performance of an advanced hydrodynamic cavitation reactor: An entropy-based analysis - Gaoju Xia; Sivakumar Manickam; Jingwei Li; Zhiqiang Yin; Wenlong Wang; Xun Sun (Ultrasonics Sonochemistry)
Hydrodynamic cavitation (HC) has emerged as a promising technique for process intensification. Recently developed advanced rotational hydrodynamic cavitation reactors (ARHCRs) have attracted significant attention from both academia and industry due to their notable economic advantages, high processing capacity, and continuous operation in specific applications. However, existing evaluation and optimization criteria for these reactors primarily rely on external parameters, often overlooking the complex micro-scale properties and energy dissipation of internal flow within the cavitation generation unit (CGU) of ARHCRs. To address this, a “simplified flow field” computational flow dynamics (CFD) approach combined with entropy production theory was employed to assess the impact of protrusion installation upstream of the CGU on ARHCR performance. The cavitation volume and total entropy generation were analyzed for protrusions of various shapes, circumferential offset angles (γ), radial positions (r), and side lengths (s). The findings revealed that energy dissipation in ARHCRs is predominantly localized in regions of flow separation and vortex formation within the CGU. Furthermore, an evaluation of multiple design factors identified that a triangular protrusion with a γ of 3.75°, r of 122.5 mm, and s of 1 mm achieved optimal performance. Comparative analysis of the flow field and vortex structures between the triangular protrusion and the baseline model demonstrated that the protrusion modifies downstream vortex dynamics, stabilizes the clearance flow field, and reduces entropy production. Additionally, these flow field modifications expand the low-pressure region, thereby enhancing cavitation performance. In this study, the employed entropy production theory identified the spatial distribution of energy loss and the dominant energy dissipation pathways within the ARHCR, thereby revealing the underlying energy loss mechanism associated with vortex formation and flow separation. These insights contribute to a deeper understanding of energy efficiency in ARHCRs and offer a foundation for optimizing reactor design to minimize energy consumption and enhance process intensification.